Pengaruh Tingkat Kualitas Pelayanan Oleh Petugas Dalam Transportasi Umum Transjakarta - Meliana Dwi Ayuningtias; Rizky Ramadhani Putri; Siti Sahara (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to find out the dimensions of service quality provided by the parties and Transjakarta Busway officers, as well as to get to know more deeply the level of user satisfaction with the services provided and by applying land transportation as research material that raises one type of land transportation, namely Transjakarta which is found in areas that focus on DKI Jakarta. This study applied a data collection method in the form of structured interviews with personal questionnaires to collect data from Transjakarta Bus users. The questionnaire contains closed and open questions concerning the user's experience of the services provided by the Transjakarta Bus. The data collected was in the form of a questionnaire made using Google Forms and from the results of the research it was possible to obtain 45% positive responses regarding the dimensions of service quality provided for services by parties and officers on Transjakarta buses. The holding of this research hopes that it will be useful in improving the quality of service available on Transjakarta buses and intends that the services provided will be better.